HASIL TES LAJU ENDAP DARAH CARA MANUAL DAN AUTOMATIK - N. Ibrahim; Suci Aprianti; M. Arif; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
Erythrocyte sedimentation rate (ESR) is a non specific test that describes changes in protein plasma and is useful to determine inflammatory case. ESR is determined by using manual and automatic. In big cities, automatic method is more popular now days, but in periphery area, manual method is still the choice. To find out correlation between the results of manual and automatic tests. Cross sectional study was carried out among 200 patients at dr. Wahidin Sudirohusodo Public Hospital of Makassar from September to October 2005. The data were analyzed using R-Square (R2) and regression test using SPSS 11.5. There is significant correlation (P<0.05) among vertical manual, oblique manual and automatic methods. R2 of automatic and vertical methods are 0.95 (the first one hour) and 0.94 (the second one hour), as well as the R2 of oblique and vertical methods are 0.62 (the first one hour) and 0.87 (the second one hour) respectively. There is correlation among the results of the three methods. To convert the result of automatic to vertical, an equation of vertical score = 4.32 + 1.00 (automatic score) can be used. Meanwhile, conversion of oblique score to vertical score is vertical score = 7.58 + 0.99 (oblique score).